2015
DOI: 10.1007/s12026-015-8720-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunology and cartilage regeneration

Abstract: The intrinsic regenerative capacity of avascular cartilage is limited. Cartilage injuries result in chronic, non-healing lesions requiring surgical management. Frequently, these surgical techniques make use of allogeneic cells and tissues. This review discusses the immune status of these materials. Cartilage allografts, often used in orthopedic and plastic surgeries, have rarely provoked a significant immune response. In whole cartilage transplants, the dense matrix produced by chondrocytes inhibits lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…PBS group (7.83 ± 0.98) vs. PRP group (6.50 ± 0.84) (p = 0.162), MSC + PBS group (4.67 ± 0.82) (p = 0.020) and MSC + PRP group (4.50 ± 0.84) (p = 0.015); PRP group vs. MSC + PBS group (p = 0.037) and MSC + PRP group (p = 0.015); and MSC + PBS group vs. MSC + PRP group (p = 0.999) to become an effective alternative treatment material because MSCs pose few problems in the donor side with harvesting, easily proliferate in culture and easily differentiate into chondrocytes (Agung et al 2006;Shirasawa et al 2006). They speculated migrated MSCs worked as a cell source for repair tissue but recent studies reported an immunomodulatory function of MSCs as another possible mechanism for tissue repair (Nam et al 2018;Smith et al 2015). Various tissues have been evaluated as sources of MSCs and synoviumderived stem cells (SDSCs) are considered to have the greatest potential for expansion and chondrogenesis, compared with other MSC sources (De Bari et al 2001;Sakaguchi et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…PBS group (7.83 ± 0.98) vs. PRP group (6.50 ± 0.84) (p = 0.162), MSC + PBS group (4.67 ± 0.82) (p = 0.020) and MSC + PRP group (4.50 ± 0.84) (p = 0.015); PRP group vs. MSC + PBS group (p = 0.037) and MSC + PRP group (p = 0.015); and MSC + PBS group vs. MSC + PRP group (p = 0.999) to become an effective alternative treatment material because MSCs pose few problems in the donor side with harvesting, easily proliferate in culture and easily differentiate into chondrocytes (Agung et al 2006;Shirasawa et al 2006). They speculated migrated MSCs worked as a cell source for repair tissue but recent studies reported an immunomodulatory function of MSCs as another possible mechanism for tissue repair (Nam et al 2018;Smith et al 2015). Various tissues have been evaluated as sources of MSCs and synoviumderived stem cells (SDSCs) are considered to have the greatest potential for expansion and chondrogenesis, compared with other MSC sources (De Bari et al 2001;Sakaguchi et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes reside in small compartmented cavities called lacunae that are surrounded by large areas of dense cartilage ECM making it difficult for these cells to move freely or migrate in response to biological cues of damaged tissue. Moreover, the lack of blood vasculature prevents the infiltration of articular cartilage by circulating immune cells [212]. Multiple approaches have been documented to help restore cartilage without surgical proceedings, but the fact remains that there are virtually no clinical treatment options in existence that completely restore damaged articular cartilage to its native state [213][214][215][216][217].…”
Section: Stimulating Articular Cartilage Repairmentioning
confidence: 99%
“…Despite the clinical benefit attained with meniscus allotransplantation and osteochondral allograft transplantation Gracitelli et al, 2015), some concerns have been raised about the potential detrimental effects of the elicited immune response. Evidence is accumulating of the immune-privileged properties of cartilage, but isolated chondrocytes and especially the bony portion of the osteochondral grafts are more immunogenic (Smith et al, 2015). Early work pointed out that allogeneic chondrocytes may elicit an immune response when injected heterotopically in rats (Romaniuk et al, 1995).…”
Section: R Sommaggio Et Al Barriers To Chondrocyte Xenotransplantationmentioning
confidence: 99%